Batimbang Salah in the customary court in Kenagarian Talang Babungo perspective 'Urf - Jufrizal, Jufrizal; Azwar, Zainal (Minhaj: Jurnal Ilmu Syariah, 2024)
This research examines the Batimbang Salah Tradition in Talang Babungo Kenagarian in terms of the perspective of 'Urf. The Batimbang Salah tradition is a customary tradition of the surrounding community in which there are several things that are contrary to the concept of U'rf and Islamic Law, one of which is that if you have not done this tradition, the younger siblings of the party concerned cannot carry out the custom of marriage in the Talang Babungo village, this kind of custom is clearly contrary to the concept of U'rf and Islamic Law, the research method that the author uses is a qualitative approach. This type of research (field research) is conducted in the field. The research was conducted in Kenagarian Talang Babungo, District Lembah Gumanti, Solok Regency. This research uses empirical law. The result of this research is that in Islamic law, everyone is recognized based on their religious identity. Meanwhile, in the customs of Kenagarian Talang Babungo and Minangkabau in general, the identity of the community is its customs and customs are the rules of daily life that have been going on for a long time and are still maintained to this day. For the people of Kenagarian Talang Babungo, to live without obeying the rules is to be uncivilized. Whereas the custom that becomes his daily clothes is adat basandi syarak, syarak basandi Kitabullah (the basic joint custom is syarak (Islamic shari'at) and the basic syarak is the Koran). but with regard to the consequences of not being carried out